Strategi Pemecahan Masalah Usaha Perikanan Purse Seine Pelagis Kecil di Kota Pangkalpinang Menyikapi Peraturan Pemisahan Kewenangan Wilayah dan Jalur Penangkapan Ikan - Taj, Kemal; Puspitasari Sudarmo, Agnes; Noviyanti, Rinda (Universitas Ekasakti, 2024)
The purpose of this study is to recommend a strategic solution to the central government for small pelagic purse seine fishery business in Pangkalpinang City in response to the regulation on the separation of authority of areas and fishing routes, namely PERMEN-KP RI Number 18 of 2021. Participants in this study are small pelagic purse seine business actors in Pangkalpinang City. The method used is a qualitative descriptive method. Data collection with direct observation and in-depth interviews. The data was analyzed by qualitative analysis and SWOT analysis. The results of the study show that the implementation of PERMEN-KP RI Number 18 of 2021 on the small pelagic purse seine fishery business in Pangkalpinang City has not gone well. Only 13% of small pelagic purse seine business actors in Pangkalpinang City have implemented the policy. Strategies to solve the problem of small pelagic purse seine fishery business in Pangkalpinang City include optimizing the implementation of the PERMEN-KP RI Number 18 of 2021 policies for fishermen to support government policies; optimizing the authority of the central government and local governments in regulating the sustainability of the fishery business; improving human resources, infrastructure, and supporting facilities and infrastructure; conducting socialization and awareness more intensively and specifically to small pelagic purse seine business actors about the importance of implementing PERMEN-KP RI Number 18 of 2021; the existence of subsidies from the central government as policymakers related to the consequences of licensing migration requirements; prioritizing sustainable local fisheries by paying attention to the conditions of certain water areas; increasing supervision by prioritizing guidance to fishermen; making special rules related to procedures withdrawal of 5% PNBP so as not to burden fishermen; the need for a review of licensing migration policies to the central government by prioritizing the interests of fishermen; as well as increasing coordination and synergy between the central government and regional agencies and related stakeholders so that the implementation of the PERMEN-KP RI Number 18 of 2021 policy can run well.